Standardized Venous Access Assessment and Safe Chemotherapy Administration to Reduce Adverse Venous Events - Arangoa Miller, Melissa; Frazier-Warmack, Victoria; Castelo, Kathrene (Clinical journal of oncology nursing, 2023)
Staff of the ambulatory infusion clinic at a Magnet-designated academic medical center observed the rates of adverse venous events, including infiltration and extravasation. An evidence-based quality improvement project was d.